2009
DOI: 10.1186/1471-2407-9-231
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Foxp3 and IDO expression is associated with sentinel lymph node metastases in breast cancer

Abstract: BackgroundThere is evidence that the immune systems of patients with breast cancer are dysfunctional. Regulatory T cells (Tregs), and IDO, an immunosuppressive enzyme, are associated with more advanced disease in some cancers and may promote immunologic tolerance to tumors. Our aim was to assess whether expression of Foxp3, a marker of Tregs, and IDO were linked with nodal metastasis in breast cancer patients. Inhibitors of IDO are available and could potentially demonstrate utility in breast cancer if IDO dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 35 publications
7
81
1
Order By: Relevance
“…Some studies also reported a correlation between high IDO1 expression in TDLN and poor clinical outcome of melanoma, suggesting that IDO1 contributes to immune evasion (22)(23)(24). However, another study performed in breast cancer did not show an enrichment of IDO1 þ cells in TDLN (25).…”
Section: Introductionmentioning
confidence: 87%
“…Some studies also reported a correlation between high IDO1 expression in TDLN and poor clinical outcome of melanoma, suggesting that IDO1 contributes to immune evasion (22)(23)(24). However, another study performed in breast cancer did not show an enrichment of IDO1 þ cells in TDLN (25).…”
Section: Introductionmentioning
confidence: 87%
“…FOXP3 expression is associated with significantly worse prognosis in node-positive BC (17). Members of our group earlier found significantly higher FOXP3 positivity in T-lymphocytes in metastatic sentinel nodes (SNs) than in tumor-free SNs, indicating local immunosupression mediated by Treg activation (18).…”
Section: Abstract Aim: Luminal a Breast Cancers (Bc) Represent Low-rmentioning
confidence: 98%
“…Mansfield et al reported that FOXP3 + cells were associated with more advanced disease in breast cancer, a finding that is proven to be true in many other cancers (54). DCs have been found to promote Treg differentiation and may become a suitable target to abrogate the development of T cell tolerance and to promote an effective immune response to breast cancer (54). As shown in Figure 5B, the recruitment of Tregs was observed in the regional lymph node premetastatic niche, and it was suppressed by COX-2 inhibition, EP3 blockade, and SDF-1 blockade.…”
Section: Discussionmentioning
confidence: 97%
“…Tregs were selectively recruited within lymphoid infiltrates and activated by mature DCs, likely through the recognition of tumor-associated antigen presentation, resulting in the prevention of effector T cell activation, immune escape, and, ultimately, tumor progression (53). Mansfield et al reported that FOXP3 + cells were associated with more advanced disease in breast cancer, a finding that is proven to be true in many other cancers (54). DCs have been found to promote Treg differentiation and may become a suitable target to abrogate the development of T cell tolerance and to promote an effective immune response to breast cancer (54).…”
Section: Discussionmentioning
confidence: 99%